Effective electroosmotic transport of water in an intrinsically microporous polyamine (PIM-EA-TB) - Mariolino Carta (Electrochemistry Communications, 2021)
Tertiary-amine-based Polymers of Intrinsic Microporosity (PIMs) provide a class of highly porous molecularly rigid materials for the electrochemical transport of both ionic and neutral species. Here, the transport of water molecules together with chloride anions (i.e. the electroosmotic drag coefficient) is studied for the intrinsically microporous polyamine PIM-EA-TB immersed in aqueous 0.01 M NaCl (i) when protonated for pH < 4 or (ii) when not protonated for pH > 4. Preliminary data suggest that in both cases a high electroosmotic drag coefficient is observed based on direct H2O transport into a D2O-filled compartment (quantified by 1H-NMR). For PIM-EA-TB there is a strong pH dependence with a higher electroosmotic drag coefficient in less acidic solutions (going from approx. 400 H2O per anion at pH 3 to approx. 4000 H2O per anion at pH 7), although the underlying absolute rate of water transport at a fixed voltage of −1 V appears to be essentially pH independent. Water transport through the PIM-EA-TB microchannels is rationalised based on the relative populations of chloride anions and of water in the micropores (essentially a ‘piston’ mechanism).